DETERMINAN TINGKAT KESETUJUAN PASANGAN USIA SUBUR TERKAIT INSTRUKSI GUBERNUR BALI NOMOR 1545 TAHUN 2019 - Semadi, I Ketut Putra; Marhaeni, Anak Agung Istri Ngurah (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The purpose of this research is to analyze effects of the age at first marriage, wife's education level, family income, and wife's employment status on the consent level of fertile age couples related to the Governor of Bali's Instruction Number 1545 of 2019. The design of this research was using quantitative method, in the form of associative. The sampling method used accidental sampling with the total sample is 99 of fertile age couples in Marga District. Data analysis technique used confirmatory factor analysis and multiple linear regression. The results showed that (1) The age at first marriage wife's education level, family income, and wife's employment status had a significant effect on the consent level of fertile age couples related to the instruction. (2) Age of first marriage and wife's education level had a negative significant effect, while family income had a positive significant effect at the consent level of fertile age couples related to the instruction. The next result is working woman tend to have a lower consent level compared to workless woman related to the Governor of Bali's Instruction Number 1545 of 2019. The results of this study are expected to be used as an evaluation material of the instruction in order to increase the consent level towards KB Krama Bali.